Yellowstone grizzly delisting rhetoric: An analysis of the online debate - Israel D. Parker; Andrea M. Feldpausch‐Parker (Wildlife Society Bulletin)
Abstract The Yellowstone ecosystem is a hotbed of environmental issues and conflicts such as endangered species management. The Yellowstone grizzly bear (Ursus arctos horribilis) delisting debate illustrates how rhetoric can contribute to fragmentation and polarization among stakeholders engaged in endangered species conflicts. The partisan view of the grizzly ideograph, and what it represented, created impediments to conflict management (e.g., mistrust and development of and/or belief in stereotypes). The debate coalesced as the U.S. Fish and Wildlife Service began proceedings to delist the Yellowstone population from the endangered species list in 2005. Our objective was to use a rhetorical analysis of the Internet‐based debate to identify strategies used by disputants in conflicts over the Endangered Species Act. By analyzing web‐based stakeholder texts from 1998 through 2009, we found that rhetoric about grizzly bears fell into three main categories of rhetorical appeal: authority, ethics, and identity. Arguments relying on these appeals contributed to destructive communication amongst stakeholders. Rhetorical strategies served to clearly define stakeholder belief systems and clarify exclusionary practices. We found as an emerging theme that perspectives toward climate change influenced perception of grizzly delisting (e.g., climate change influences grizzly bear food availability). The Endangered Species Act's lack of directives regarding anthropogenic climate change further complicated the debate. We demonstrated how rhetorical analyses can reveal disputants' preferred social control frameworks. This provides important information to managers seeking to promote common ground between otherwise conflicted stakeholders that leads to legitimate and lasting policy decisions. © 2013 The Wildlife Society.